Calculations of electron inelastic mean free paths. IX. Data for 41 elemental solids over the 50 eV to 30 keV range - Tanuma, S.; Powell, C. J.; Penn, D. R. (Surface and interface analysis, 2011)
We have calculated inelastic mean free paths (IMFPs) for 41 elemental solids (Li, Be, graphite, diamond, glassy C, Na, Mg, Al, Si, K, Sc, Ti, V, Cr, Fe, Co, Ni, Cu, Ge, Y, Nb, Mo, Ru, Rh, Pd, Ag, In, Sn, Cs, Gd, Tb, Dy, Hf, Ta, W, Re, Os, Ir, Pt, Au and Bi) for electron energies from 50 eV to 30 keV. The IMFPs were calculated from experimental optical data using the full Penn algorithm for energies up to 300 eV and the simpler single‐pole approximation for higher energies. The calculated IMFPs could be fitted to a modified form of the Bethe equation for inelastic scattering of electrons in matter for energies from 50 eV to 30 keV. The average root‐mean‐square (RMS) deviation in these fits was 0.48%. The new IMFPs were also compared with IMFPs from the predictive TPP‐2M equation; in these comparisons, the average RMS deviation was 12.3% for energies between 50 eV and 30 keV. This RMS deviation is almost the same as that found previously in a similar comparison for the 50 eV–2 keV range. Relatively large RMS deviations were found for diamond, graphite and cesium. If these three elements were excluded in the comparison, the average RMS deviation was 9.2% between 50 eV and 30 keV. We found satisfactory agreement of our calculated IMFPs with IMFPs from recent calculations and from elastic‐peak electron‐spectroscopy experiments. Copyright © 2010 John Wiley & Sons, Ltd.